Physico-chemical quality and storage stability of fermented Chhana whey beverages - saha, priti; ray, pinaki ranjan (Indian Journal of Dairy Science, 2017)
Physico- chemical quality and storage stability of probiotic fermented beverages prepared by fermentation of chhana whey with L. acidophilus (Beverage I) and L. bulgaricus (Beverage II) respectively were studied. Both the beverages were prepared by the addition of the cultures @ 2% (w/v). The pH of the beverage I and beverage II were found to be 3.59 and 3.65 respectively. The total solid, fat, protein and lactose content were found to be 22.30, 0.18, 0.25 and 4.39% respectively in beverage I and 22.00, 0.17, 0.232 and 4.35 respectively in beverage II. The sensory score of the beverage I (7.77) was slightly higher than beverage II (7.59).Both the beverage had a shelf life of 10 days when stored at 7+ 20C. The average lactobacilli count of 7.32+0.03 and 7.28+ 0.02 cfu/ml in Beverage I and II respectively were observed on the 10th day of storage. Growth of yeasts, molds and coliforms were not observed during the storage period. Hence both L. acidophilus and L. bulgaricus could successfully be used @ 2% (w/v) in the preparation of probiotic fermented chhana whey beverage.Â Â